Efeito do regime hídrológico na estruturação das assembleias de peixes da sub-bacia do baixo Rio Roosevelt no sudoeste da bacia amazônica - Anjos, Marcelo Rodrigues dos (2017)
This study was carried out in the sub-basin of the lower Roosevelt River in the southwest of the state of Amazonas in order to analyze the influence of the hydrological regime on environmental gradients that could influence the structures of fish assemblages. The collections were carried out between November 2012 and August 2013 on a quarterly basis to estimate the catch effort (CPUE) of the data obtained from the waiting networks. During the study a total of 5135 specimens were captured, these numbers being distributed in seven orders, 29 families, 101 genera and 186 species. Multivariate analyzes of NPMANOVA were used to evaluate the influence of the period on the environmental variables demonstrating values of p <0.001 and R2 adjustment above 99% explained by (33%) where F3,113 = 19,154 and the value observed for stability Of the standard p <0.001. Likewise, the collection period showed a strong influence on the structure of fish assemblages for the study area, explained by 8.1%, followed by depth with 6.6%, temperature 3.4% and dissolved oxygen 3, 1% being the other variables represented by lower values. Only the total dissolved solids (TDS) variable had no influence on the fish community structure for the sample area. The NMDS and similarity dendrogram using the Sorensen coefficient analysis reaffirm this tendency, giving robustness to the data generated with the formation of four distinct emergent groups characterized by the collection periods, in addition to the group of species that occur indistinctly throughout the Species, which are widely distributed in addition to resident species. The study area and its associated streams ealed a maintenance of the general community structure based on the abundance of common species, and great variation in the composition of low abundance species. Common species represent a high probability of detection in the lower Roosevelt River sub-basin and give the fish assemblage a predictable structure along the environmental gradient defined therein as a hydrological regime represented by (flood, full, ebb and dry). Qualitative and quantitative monitoring programs of fish biodiversity may be centered on the distribution of abundances of common species, except in cases of endemism, when special attention should be paid to the distribution in relation to direct and indirect interdependence with the community structure. The present work was part of the project "Study and monitoring of the temporal variation of the fish fauna in the Roosevelt River basin - National Park of the Amazonian Fields". The information generated is of fundamental importance and should be considered to identify potential for exploitation, to understand ecological dynamics and its current limits, so that these can subsidize management activities and territorial planning, including guiding in the promotion of new public policies.